Study to Support Improvement of the PNHA Components: Expenditures on Employer-provided Health Care and Private Schools Health Services - Rachel H. Racelis (Philippine Institute for Development Studies (PIDS), 2014)
The expenditures for employer-provided health care in private establishments and for student health services in private schools are two components estimated in the Philippine National Health Accounts (PNHA). The basic methodology for producing the annual estimates of the two components have remained the same since the first PNHA was produced in 1994 and estimation procedures had continued to use through the years the parameters (average costs) generated from the 1993-1994 establishments and private schools surveys. The surveys on health expenditures of private establishments and private schools were conducted again in 2013-2014 as part of this study. Results from the new surveys are used to generate the updated parameters for PNHA estimation. Additionally, results from the survey provide detail on curative care provision and preventive health care activities of establishments and private schools.
Keywords: 330; Philippines; health; Philippine National Health Accounts; employer-provided health care; private schools health services; health accounts approach